Human Leukocyte Antigen-Class I Alleles and the Autoreactive T Cell Response in Psoriasis Pathogenesis - Prinz, Jörg Christoph (Frontiers in Immunology, 2018)
Psoriasis is a complex immune-mediated inflammatory skin disease characterized by T-cell driven epidermal hyperplasia. It occurs on a strong genetic predisposition. The human leukocyte antigen (HLA)-class I-allele HLA-C*06:02 on psoriasis susceptibility locus 1 (PSORS1 on 6p21.3) is the main psoriasis risk gene. Other HLA-class I alleles encoding HLA molecules and presenting overlapping peptide repertoires show associations with psoriasis as well. Outside the major histocompatibility (MHC) region, genome-wide association studies identified more than 60 psoriasis-associated common gene variants exerting only modest individual effects. They mainly refer to innate immune activation and the IL-23/Th/c17 pathway. Given their strong risk association, explaining the role of the HLA-risk alleles is essential for elucidating psoriasis pathogenesis. Psoriasis lesions develop upon epidermal infiltration, activation and expansion of CD8+ T cells. The unbiased analysis of a paradigmatic Vα3S1/Vβ13S1-T-cell receptor (TCR) from a pathogenic epidermal CD8+ T-cell clone of an HLA-C*06:02+ psoriasis patient had revealed that HLA-C*06:02 directs an autoimmune response against melanocytes through autoantigen presentation, and it identified a peptide form ADAMTS-like protein 5 (ADAMTSL5) as an HLA-C*06:02-presented melanocyte autoantigen. These data demonstrate that psoriasis is an autoimmune disease, where the predisposing HLA-class I-alleles promote organ-specific inflammation through facilitating a T-cell response against a particular skin-specific cell population. This review discusses the role of HLA-class I alleles in the pathogenic psoriatic T-cell immune response. It concludes that as a principle of T-cell driven HLA-associated inflammatory diseases proinflammatory traits drive autoimmunity in the context of certain HLA molecules that present particular autoantigens.